Aplikasi Smarthome Berbasis IoT Menggunakan Android Studio - Ibnu Kurniawan; Sidhiq Andriyanto; Indra Dwisaputra (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The Internet of Things (IoT) allows the integration of hardware with internet networks for remote control and regulation. IoT is a technology that allows various devices to connect and communicate with each other over the internet, thus enabling efficient automation. This research develops a Smarthome application called EDITH that operates based on IoT. The app allows control of the lighting device through a smartphone with additional features such as scheduling, energy monitoring, and usage history. The system uses the NodeMCU ESP32 as a microcontroller that is integrated with the Adafruit.io server. The test results show that EDITH can function effectively in controlling the lights remotely, with a user satisfaction rate of 84%.